Big and Little Histories Sizing Up Ethics in Historiography - Hughes-Warrington, Marnie (Taylor & Francis, 2022)
"This book introduces students to ethics in historiography through an exploration of how historians in different times and places have explained how history ought to be written and how those views relate to different understandings of ethics. No two histories are the same. The book argues that this is a good thing because the differences between histories are largely a matter of ethics. Looking to histories made across the world and from ancient times until today, readers are introduced to a wide variety of approaches to the ethics of history, including well-known ethical approaches, such as the virtue ethics of universal historians, and utilitarian approaches to collective biography writing while also discovering new and emerging ideas in the ethics of history. Through these approaches, readers are encouraged to challenge their ideas about whether humans are separate from other living and non-living things and whether machines and animals can write histories. The book looks to the fundamental questions posed about the nature of history making by Indigenous history makers and asks whether the ethics at play in the global variety of histories might be better appreciated in professional codes of conduct and approaches to research ethics management. Opening up the topic of ethics to show how historians might have viewed ethics differently in the past, the book requires no background in ethics or history theory and is open to all of those with an interest in how we think about good histories."